2021
DOI: 10.3390/agronomy11071415
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Microbial Transformation of Nitrogen Compounds in the Light of Integrated Crop Management

Abstract: Nitrogen (N) is widely distributed in the lithosphere, hydrosphere, atmosphere and biosphere. It is a basic component of every plant cell as well as microorganisms, as a component of proteins, nucleic acids and chlorophyll. It enters soil with organic and mineral fertilizers, plant and animal residues and biological nitrogen fixation. There are various forms of nitrogen in soil, and this element is usually transformed by microorganisms. The transformation of nitrogen compounds (ammonification, nitrification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 190 publications
(194 reference statements)
1
30
0
1
Order By: Relevance
“…The provision of manure on latosol soil has excellent benefits, such as the availability of more P elements. This is because the results of the decomposition of organic matter in the form of humic acids that form chelate bonds with Al and Fe ions can reduce the solubility of Al and Fe ions and also release P, which is fixed by Al and Fe so that P availability increases (Tonks et al 2017;Grzyb et al 2021;Sukmasari et al 2021). Organic matter would improve cation exchange capacity (CEC) and form a chelated cation (Sudadi et al 2018;Agus et al 2019;Dai et al 2020).…”
Section: Results and Discussion Soybean's Growth On Marginal Soilmentioning
confidence: 99%
“…The provision of manure on latosol soil has excellent benefits, such as the availability of more P elements. This is because the results of the decomposition of organic matter in the form of humic acids that form chelate bonds with Al and Fe ions can reduce the solubility of Al and Fe ions and also release P, which is fixed by Al and Fe so that P availability increases (Tonks et al 2017;Grzyb et al 2021;Sukmasari et al 2021). Organic matter would improve cation exchange capacity (CEC) and form a chelated cation (Sudadi et al 2018;Agus et al 2019;Dai et al 2020).…”
Section: Results and Discussion Soybean's Growth On Marginal Soilmentioning
confidence: 99%
“…The main reactions that control the dynamics of nitrogen in soil and groundwater are mineralisation, volatilisation, nitrification, and denitrification, for the most part, mediated by microorganisms that play a key role in the fate of nitrogen in terrestrial ecosystems. [77,78]. Therefore, monitoring the microbial communities involved in the nitrogen cycle represents a valuable tool for determining potential sources of nitrates affecting surface and groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that amino acids play a key role in plant root growth and microbial colonization, symbiotic interactions, and pathogenesis in the rhizosphere [94]. Amino acids are considered a key intermediary in the soil nitrogen cycle, and function as carbon and nitrogen sources for both microorganisms and plants, in synthesis and regulation of auxin activity and biofilm formation and disassembly [95]. Therefore, the nucleic acid processing for protein synthesis pathway, which was found active in biosolid-enriched soils, could be an indicator of intrinsic amino acid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%